2009
DOI: 10.1051/0004-6361/200811520
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Newton second law in the regime of small accelerations

Abstract: It has been pointed out that the Newtonian second law can be tested in the very small acceleration regime by using the combined movement of the Earth and Sun around the Galactic center of mass. It has been shown that there are only two brief intervals during the year in which the experiment can be completed, which correspond to only two specific spots on the Earth surface. An alternative experimental setup is presented to allow the measurement to be made on Earth at any location and at any time.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…An improvement on this idea was suggested in Ref. [16]. A simpler approach has recently been proposed by Das and Patitsas [17], who made use of free falling laboratories and assumed the validity of the SEP.…”
Section: Introductionmentioning
confidence: 99%
“…An improvement on this idea was suggested in Ref. [16]. A simpler approach has recently been proposed by Das and Patitsas [17], who made use of free falling laboratories and assumed the validity of the SEP.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have attempted to extract information from double and multiple galaxy clusters on the nature of gravity and dark matter on galactic cluster (1 Mpc) distance scales, and up to now this was mainly centred on analysing the 1E 065756 cluster. Farrar & Rosen (2006), Brownstein & Moffat (2007), Angus & McGaugh (2008), Schmidt, Vikhlinin & Hu (2009) and De Lorenci, Faundez‐Abans & Pereira (2009) are among those who investigated whether modifications to gravity are needed to fit the available dynamical data. Springel & Farrar (2007), Pointecouteau & Silk (2005) and Hayashi & White (2006), however, indicated that modifications are unneccesary.…”
Section: Introductionmentioning
confidence: 99%
“…It may or may not be practical, but if not, there are plenty of other options to contemplate. At least three of them have been discussed in the literature [3,5]. The main thrust of this paper is to draw attention to these alternatives.…”
Section: Introductionmentioning
confidence: 99%
“…Another approach [5] exploits the same basic idea of cancellation, but in a different experimental set-up. The key point is to introduce extra, man-made centrifugal forces into play (in addition to the usual, terrestrial ones).…”
Section: Introductionmentioning
confidence: 99%